Education And Strengthening of Al Chasanah Students In Preventing Hiv/Aids Among Youth - Erlina Puspitaloka Mahadewi; Intan Silviana Mustikawati; Mohamad Reza Hilmy; Zairil Zairil; Sukardi Sukardi; Arman Harahap (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The present study reports the newest comprehensive study after pandemic era for the Infectious Disease acquired Immunodeficiency Syndrome (AIDS), caused by the Human Immunodeficiency Virus (HIV) the number of people living with HIV/AIDS (ODHA) continues to grow, this needs to be balanced with efforts to prevent the transmission of HIV/AIDS. The present study reports the comprehensive study after pandemic era for the prevention and education of Infectious Disease acquired Immunodeficiency Syndrome (AIDS) among youth in Al-Chasanah high school, Jakarta Indonesia, caused by the Human Immunodeficiency Virus (HIV) the number of people living with HIV/AIDS (ODHA) continues to grow, this needs to be balanced with efforts to prevent the transmission of HIV/AIDS since earlier. This type of research was quantitative with educational preventive counseling. The characteristics of adolescents who are unstable so that they are easily influenced by the environment, it is necessary to instill various positive information to support adolescent cognitive development. It is hoped that adolescents will have positive (cognitive) knowledge which will continue in other aspects of attitudes, namely positive (affective) feelings that arise in adolescents, so that they also influence the tendency of adolescents to behave positively (conatively). In conclusion, that every student can understand and experience progress after the distribution of material. This can be compared with the pre-test and post-test diagrams where the average student can answer the test with the same questions before and after the distribution of material education.